Legal Protection of the Nation's Cultural Identity in the Era of Globalisation - Yulianah, Yuyun; M Rozi, Mumuh; Raihan Azhari Kusworo, Fuji; Hadi Aulia, Salsabila; Kurniawan, Rendy (Universitas Semarang, 2025)
Indonesia is blessed with an extraordinary and diverse cultural wealth, stretching from Sabang to Merauke. Each region has unique traditions, customs, languages, arts and local wisdom that reflect the nation's identity. This cultural wealth is a valuable heritage that has been passed down from generation to generation and has become an integral part of Indonesian life. In the era of globalisation, Indonesian culture is faced with various complex challenges. The heavy influence of foreign culture, liberalisation, westernisation, and internationalisation is eroding the existence of the nation's culture. This can threaten the national identity and cultural heritage that has been preserved for centuries. This research uses a normative juridical method to examine various efforts to preserve Indonesian culture in the era of globalisation. This approach is carried out by analysing various laws and regulations, legal norms, and rules relating to cultural preservation. Preserving Indonesian culture is the shared responsibility of all Indonesian people. This preservation effort must be carried out comprehensively and sustainably, by involving various parties, from the government, the community, to the younger generation.